2008
DOI: 10.1037/0022-006x.76.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Nonsuicidal self-injury in young adolescent girls: Moderators of the distress-function relationship.

Abstract: This study examined nonsuicidal self-injury (NSSI) in a community sample of young adolescent girls. Potential moderators of the relationships between different types of distress (internal and interpersonal) and particular functions of NSSI (emotion-regulation and interpersonal) were explored. Participants included 94 girls (49% Hispanic; 25% African American) ages 10-14 years who completed questionnaires regarding self-injurious behavior and other constructs of interest. Fifty-six percent of girls (n = 53) rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
203
3
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(237 citation statements)
references
References 63 publications
24
203
3
7
Order By: Relevance
“…As outlined in the top left corner of Figure 2, this creates the four functions of automatic negative reinforcement (i.e., removal or distraction from aversive thoughts or feelings), automatic positive reinforcement (i.e., feeling generation), social positive reinforcement (i.e., obtaining a favorable social response), and social negative reinforcement (i.e., removal or distraction from external events). The structural validity, internal consistency reliability, and construct validity of the FFM have been supported in our earlier work (Nock & Prinstein, 2004, 2005 and the model has received independent support from other research groups (e.g., Hilt, Cha, & Nolen-Hoeksema, 2008;Lloyd-Richardson, Perrine, Dierker, & Kelley, 2007).…”
Section: Elaboration On the Social Functions Of Nssimentioning
confidence: 55%
See 1 more Smart Citation
“…As outlined in the top left corner of Figure 2, this creates the four functions of automatic negative reinforcement (i.e., removal or distraction from aversive thoughts or feelings), automatic positive reinforcement (i.e., feeling generation), social positive reinforcement (i.e., obtaining a favorable social response), and social negative reinforcement (i.e., removal or distraction from external events). The structural validity, internal consistency reliability, and construct validity of the FFM have been supported in our earlier work (Nock & Prinstein, 2004, 2005 and the model has received independent support from other research groups (e.g., Hilt, Cha, & Nolen-Hoeksema, 2008;Lloyd-Richardson, Perrine, Dierker, & Kelley, 2007).…”
Section: Elaboration On the Social Functions Of Nssimentioning
confidence: 55%
“…In support of this theory in the case of NSSI, recent studies have reported a significant relation between peer victimization and engagement in NSSI (Hilt et al, 2008;Photos, Nock, & Prinstein, 2006). Moreover, a more specific relation has been demonstrated between identification with Goth subculture and engagement in both suicidal and non-suicidal selfinjury (Young, Sweeting, & West, 2006), and tattooing and body piercing also have been linked to higher rates of suicidal and other risky behaviors (Carroll, Riffenburgh, Roberts, & Myhre, 2002).…”
Section: Signals Of Strength and Fitnessmentioning
confidence: 94%
“…Therefore, when an adolescent is experiencing emotional distress, the affective processing system of physical pain may be inadvertently activated in order to motivate the individual to seek social support and attachment. Social distress, in the form of feeling isolated or victimized, is also a common reason for NSSI (Hilt et al 2008). It is possible that, in individuals who engage in NSSI, this pathway is activated to regulate emotions through physical pain, although this paradigm has yet to be tested in adolescent self-injuring populations.…”
Section: Social Distress and Painmentioning
confidence: 99%
“…cutting, burning, or hitting oneself) become a major public health concern [1]. It is particularly pertinent to adolescents, with the prevalence ranging from 14-56% [2][3][4]. NSSI has been included in the newest version of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) as a new disorder, and was proved to be a potent risk factor for later suicide attempts [5][6][7], indicating that this problematic behavior deserves more attention.…”
Section: Introductionmentioning
confidence: 99%